Síntese e caracterização de nanocatalisadores de platina suportados aplicados à reação de reforma do metano - Meira, Débora Motta (2010)
Colloidal Nanoparticles of Platinum (Pt-NPs) were obtained by reducing hexacloroplatinic acid with ethylene glycol in the presence of polyvinylpyrrolidone (PVP) as protective agent of the particles. Two methods of synthesis were performed which differed by the ratio PVP / Pt used. The synthesis of nanoparticles was accompanied by measures in the UV-visible from of which it was possible to determine the end of the reaction. The Pt-NPs were characterized by Transmission Electron Microscopy (TEM) that determined the average diameter of particles (~ 2.0 nm). After the synthesis, the Pt-NPs were incorporated into the supports of alumina and alumina promoted with cerium and cerium-zirconium which were prepared by sol-gel method. Supporters with nanoparticles incorporated were then subjected to heat treatment have sought the formation of stable catalysts and without the presence of protective polymer, as this could affect the activity of the catalyst by covering the active sites. Through X-ray diffraction and TEM images it was possible to monitor the stability of samples after heat treatment and the samples that were synthesized with higher PVP were more stable. Measures of X-ray absorption fine structure (XAFS) spectroscopy in situ allowed the characterization of the samples in the reaction atmosphere. Through the analysis of extended X-ray absorption fine structure (EXAFS) was observed morphological changes in the particles caused by the increase in temperature showing that there is an increase in the number of atoms of low coordination when samples are heated which favors the reaction of steam reforming of methane. Through studies of X-ray absorption near edge structure (XANES) in the edges L2 and L3 of Pt was possible to monitor how the electron density of the catalysts varies in reaction conditions. Moreover, the catalysts were also tested catalysts. Measures of dispersion were obtained by the reaction of dehydrogenation of cyclohexane and catalysts made of alumina promoted with cerium and cerium-zirconium displayed less dispersion due to the coating caused by the support. The catalysts in which the particles were synthesized with a higher amount of PVP, because of its stability, were subjected to the reaction of steam reforming of methane and proved active. This reaction was used to calculate the value of the apparent activation energy. The catalysts containing promoters were more active than the catalyst only alumina thus showing the role of support in this reaction. Therefore, this system has proved very interesting to study the catalytic properties in reactions sensitive to the structure since the nanoparticles present are monodispersed and the catalyst is stable under reaction conditions allowing the study of structural and electronic properties.